Conservation implications of low contemporary connectivity along the Mid‐Atlantic Ridge in hydrothermal vent gastropods - E. Portanier; A. Tran Lu Y; F. Pradillon; C. Daguin‐Thiébaut; S. Ruault; P. Collins; E. Omnes; S. Fuchs; J. Carlsson; D. Jollivet; M. Matabos (Conservation Biology, 2026)
Polymetallic sulfide deposits produced at hydrothermal vent fields are targets for mining exploitation along the Mid‐Atlantic Ridge, threatening the functioning and resilience of vent ecosystems that provide multiple ecosystem services. Knowledge about connectivity between vents will inform conservation practices. The present‐day genetic structure and demographic history of the two vent‐dwelling gastropod species, Lepetodrilus atlanticus and Peltospira smaragdina , were investigated using more than 15,000 single‐nucleotide polymorphisms and mt Cox1 sequences. Each species comprised three genetic groups. Genetic breaks were stronger for L. atlanticus , separating three distinct operational taxonomic units (5°S, Broken Spur at 29°N, and the Azorean vent fields near 37°N). Peltospira smaragdina was also geographically separated into three groups: Broken Spur, TAG, and Snake Pit (23–29°N); Lucky Strike (37°N); and Moytirra (45°N). A semipermeable zone was detected south of Rainbow (35°N), similar to that of vent mussels in this area, suggesting the presence of a multispecies hybrid zone. Demographic inferences supported secondary contact between most pairs of metapopulations for both species, but the time since contact was insufficient for allele frequencies to rehomogenize. Gene flow between vent fields may be sporadic and rare or restricted by genetic barriers. The fragmentation of species into isolated metapopulations may reduce their resilience to disturbance and create the need for specific conservation measures. Isolated populations (e.g., Moytirra for P. smaragdina , 5°S and Broken Spur for L. atlanticus ), source populations (e.g., Lucky Strike for P. smaragdina ), admixture areas, and sites that may act as stepping stones within a metapopulation must be protected from deep‐sea mining. An average distance of

Quaternary terrace formation in response to climate, regional uplift and local normal faulting: The Danube terrace staircase of Vienna - B.C. Salcher; S.M. Neuhuber; J.-C. Otto; T. Payer; C. Lüthgens; S. Fuchs; A. Flores-Orozco; J. Nørgaard; S. Grupe; O. Marchhart; A. Wieser; J. Lachner; et al. (Quaternary Science Reviews, 2026)

Decode-STS: Deciphering the landscape of canine soft-tissue sarcoma using spatially defined proteomics and transcriptomics - D. Fuchs; E. Markkanen; H. Ech-Cherif; S. Aghaabbasi; A. Pöschel; E. Beebe; L. Laura; W. Wolski; F. Guscetti; M. Nolff (Journal of Comparative Pathology, 2025)

Antibacterial Synergism of Fluoxetine and Paroxetine with Ceftriaxone, Plasmid DNA Cleavage and Repositioning - Vitória S. Foletto; Marissa B. Serafin; Augusto D. da Mota; Taciéli F. da Rosa; Angelita Bottega; Sara L. Marion; Bruno R. de Paula; Laísa N. Franco; Luana B. Fuchs; Rosmari Hörner (Current Microbiology, 2025)

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Contrasting Population Trajectories of Temperate Reef Fishes and Invertebrates Following Seasonal and Multi‐Decadal Temperature Change - Yann Herrera Fuchs; Graham J. Edgar; Neville S. Barrett; Lara Denis‐Roy; Shenae Y. Willis; Hunter Forbes; Rick D. Stuart‐Smith (Global Change Biology, 2025)
Temperature perturbations from climate change affect ecosystems through short‐term pulse events, such as heatwaves, and chronic long‐term shifts. Temperate rocky reef ecosystems have been observed to show substantial ecological change as a result of short‐term temperature fluctuations, but the longer‐term impacts of temperature change remain poorly understood. Here, we investigate temperate reef fishes and mobile invertebrates along Tasmania's east coast, contrasting trends in species richness, abundance, and community structure across seasons within a year to those observed over three decades of warming. Fishes exhibited dynamic seasonal shifts, but interannual changes in richness and abundance balanced out over decades with limited overall net change. In contrast, invertebrate communities changed little seasonally but suffered significant long‐term losses. Our study revealed short‐term ecological changes driven by temperature to be incongruent with long‐term shifts. Species responded in varying ways, depending on life history and ecology. Fishes apparently tracked short temperature pulses, while less mobile invertebrates, such as echinoderms and molluscs, tolerated short‐term fluctuations but exhibited long‐term decline. Multi‐scale studies across a broad range of taxa are needed to clarify thermal responses. The most vulnerable taxa—those facing long‐term thermal stress—may be overlooked through decisions based on short‐term studies, risking major biodiversity loss.

Effectiveness of ozone nanobubble treatments on high biomass cyanobacterial blooms: A mesocosm experiment and field trial - Justin D. Chaffin; David E. Berthold; Eugene C. Braig; Josh D. Fuchs; Rachel S. Gabor; Stephen J. Jacquemin; Haley E. Kuhn; Lillian D. Labus; H. Dail Laughinghouse; Forrest W. Lefler; Heath E. Mash; Heather A. Raymond; et al. (Journal of Environmental Management, 2024)

Mixture toxicity study of two metal oxide nanoparticles and chlorpyrifos on Eisenia andrei earthworms - Marcela I. Cáceres-Wenzel; Florencia N. Bernassani; Julio S. Fuchs; Eduardo Cortón; Adriana C. Cochón (Environmental Science and Pollution Research, 2024)

The transition to electrified vehicles: Evaluating the labor demand of manufacturing conventional versus battery electric vehicle powertrains - Turner Cotterman; Erica R.H. Fuchs; Kate S. Whitefoot; Christophe Combemale (Energy Policy, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

When colors mislead: Genomics and bioacoustics prompt re-classification of Asian flycatcher radiation (Aves: Niltavinae) - Kritika M. Garg; Chyi Yin Gwee; Balaji Chattopadhyay; Nathaniel S. Ng; Dewi M. Prawiradilaga; Gabriel David; Jérôme Fuchs; Hung Le Manh; Jonathan Martinez; Urban Olsson; Vuong Tan Tu; Sophea Chhin; et al. (Molecular Phylogenetics and Evolution, 2024)

A multi-criteria drought resistance assessment of temperate Acer, Carpinus, Fraxinus, Quercus, and Tilia species - C. Leuschner; S. Fuchs; P. Wedde; E. Rüther; B. Schuldt (Perspectives in Plant Ecology, Evolution and Systematics, 2024)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Toxic elements in arctic and sub-arctic brown bears: Blood concentrations of As, Cd, Hg and Pb in relation to diet, age, and human footprint - Boris Fuchs; Kyle Joly; Grant V. Hilderbrand; Alina L. Evans; Ilia Rodushkin; Lindsey S. Mangipane; Buck A. Mangipane; David D. Gustine; Andreas Zedrosser; Ludovick Brown; Jon M. Arnemo (Environmental Research, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Repositioning of Benzodiazepine Drugs and Synergistic Effect with Ciprofloxacin Against ESKAPE Pathogens - Taciéli F. da Rosa; Marissa B. Serafin; Vitória S. Foletto; Laísa N. Franco; Bruno R. de Paula; Luana B. Fuchs; Luciano Calegari; Rosmari Hörner (Current Microbiology, 2023)

A desiccated dual-species subaerial biofilm reprograms its metabolism and affects water dynamics in limestone - F. Villa; N. Ludwig; S. Mazzini; L. Scaglioni; A.L. Fuchs; B. Tripet; V. Copié; P.S. Stewart; F. Cappitelli (Science of The Total Environment, 2023)

Lipid droplets and perilipins in canine osteosarcoma. Investigations on tumor tissue, 2D and 3D cell culture models - N. Leitner; J. Hlavatý; R. Ertl; S. Gabner; A. Fuchs-Baumgartinger; Ingrid Walter (Veterinary Research Communications, 2022)
Lipid droplets were identified as important players in biological processes of various tumor types. With emphasis on lipid droplet-coating proteins (perilipins, PLINs), this study intended to shed light on the presence and formation of lipid droplets in canine osteosarcoma. For this purpose, canine osteosarcoma tissue samples ( n = 11) were analyzed via immunohistochemistry and electron microscopy for lipid droplets and lipid droplet-coating proteins (PLINs). Additionally, we used the canine osteosarcoma cell lines D-17 and COS4288 in 2D monolayer and 3D spheroid (cultivated for 7, 14, and 21 days) in vitro models, and further analyzed the samples by means of histochemistry, immunofluorescence, molecular biological techniques (RT-qPCR, Western Blot) and electron microscopical imaging. Lipid droplets, PLIN2, and PLIN3 were detected in osteosarcoma tissue samples as well as in 2D and 3D cultivated D-17 and COS4288 cells. In spheroids, specific distribution patterns of lipid droplets and perilipins were identified, taking into consideration cell line specific zonal apportionment. Upon external lipid supplementation (oleic acid), a rise of lipid droplet amount accompanied with an increase of PLIN2 expression was observed. Detailed electron microscopical analyzes revealed that lipid droplet sizes in tumor tissue were comparable to that of 3D spheroid models. Moreover, the biggest lipid droplets were found in the central zone of the spheroids at all sampling time-points, reaching their maximum size at 21 days. Thus, the 3D spheroids can be considered as a relevant in vitro model for further studies focusing on lipid droplets biology and function in osteosarcoma.

SARS-CoV-2 and seasonal influenza: similarities and disparities - Halima Dabaja-Younis; Eyal Fuchs; Nadeem Shorbaji; Tal Appel; Noah Carmon; Yael Shachor-Meyouhas; Manfred S. Green; Khetam Hussein (Archives of Virology, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Metagenomic analysis of nepoviruses: diversity, evolution and identification of a genome region in members of subgroup A that appears to be important for host range - J. M. Hily; N. Poulicard; J. Kubina; J. S. Reynard; A. S. Spilmont; M. Fuchs; O. Lemaire; E. Vigne (Archives of Virology, 2021)
Data mining and metagenomic analysis of 277 open reading frame sequences of bipartite RNA viruses of the genus Nepovirus , family Secoviridae , were performed, documenting how challenging it can be to unequivocally assign a virus to a particular species, especially those in subgroups A and C, based on some of the currently adopted taxonomic demarcation criteria. This work suggests a possible need for their amendment to accommodate pangenome information. In addition, we revealed a host-dependent structure of arabis mosaic virus (ArMV) populations at a cladistic level and confirmed a phylogeographic structure of grapevine fanleaf virus (GFLV) populations. We also identified new putative recombination events in members of subgroups A, B and C. The evolutionary specificity of some capsid regions of ArMV and GFLV that were described previously and biologically validated as determinants of nematode transmission was circumscribed in silico . Furthermore, a C-terminal segment of the RNA-dependent RNA polymerase of members of subgroup A was predicted to be a putative host range determinant based on statistically supported higher π (substitutions per site) values for GFLV and ArMV isolates infecting Vitis spp. compared with non- Vitis -infecting ArMV isolates. This study illustrates how sequence information obtained via high-throughput sequencing can increase our understanding of mechanisms that modulate virus diversity and evolution and create new opportunities for advancing studies on the biology of economically important plant viruses.

Endogenous anandamide and self-reported pain are significantly reduced after a 2-week multimodal treatment with and without radon therapy in patients with knee osteoarthritis: a pilot study - M. Gaisberger; J. Fuchs; M. Riedl; S. Edtinger; R. Reischl; G. Grasmann; B. Hölzl; F. Landauer; H. Dobias; F. Eckstein; M. Offenbächer; M. Ritter; et al. (International Journal of Biometeorology, 2021)
Multimodal therapies comprising spa applications are widely used as non-pharmaceutical treatment options for musculoskeletal diseases. The purpose of this randomized, controlled, open pilot study was to elucidate the involvement of the endocannabinoid system in a multimodal therapy approach. Twenty-five elderly patients with knee osteoarthritis (OA) received a 2-week spa therapy with or without combination of low-dose radon therapy in the Bad Gastein radon gallery. A 10-point numerical rating scale (pain in motion and at rest), WOMAC questionnaire, and the EuroQol-5D (EQ-5D) questionnaire were recorded at baseline, and during treatment period at weeks one and two, and at 3-month and 6-month follow-ups. Plasma levels of the endocannabinoid anandamide (AEA) were determined at baseline and at 2 weeks, and serum levels of several cartilage metabolism markers at all five time-points. A significant and sustained reduction of self-reported knee pain was observed in the study population, but no further significant effect of the additional radon therapy up and above base therapy. This pain reduction was accompanied by a significant reduction of AEA plasma levels during treatment in both groups. No significant differences were seen in serum marker concentrations between the groups treated with or without radon, but a small reduction of serum cartilage degradation markers was observed during treatment in both groups. This is the first study investigating AEA levels in the context of a non-pharmacological OA treatment. Since the endocannabinoid system represents a potential target for the development of new therapeutics, further studies will have to elucidate its involvement in OA pain.

Missense and truncating variants in CHD5 in a dominant neurodevelopmental disorder with intellectual disability, behavioral disturbances, and epilepsy - Ilaria Parenti; Daphné Lehalle; Caroline Nava; Erin Torti; Elsa Leitão; Richard Person; Takeshi Mizuguchi; Naomichi Matsumoto; Mitsuhiro Kato; Kazuyuki Nakamura; Stella A. de Man; Heidi Cope; et al. (Human Genetics, 2021)
Located in the critical 1p36 microdeletion region, the chromodomain helicase DNA-binding protein 5 ( CHD5 ) gene encodes a subunit of the nucleosome remodeling and deacetylation (NuRD) complex required for neuronal development. Pathogenic variants in six of nine chromodomain (CHD) genes cause autosomal dominant neurodevelopmental disorders, while CHD5 -related disorders are still unknown. Thanks to GeneMatcher and international collaborations, we assembled a cohort of 16 unrelated individuals harboring heterozygous CHD5 variants, all identified by exome sequencing. Twelve patients had de novo CHD5 variants, including ten missense and two splice site variants. Three familial cases had nonsense or missense variants segregating with speech delay, learning disabilities, and/or craniosynostosis. One patient carried a frameshift variant of unknown inheritance due to unavailability of the father. The most common clinical features included language deficits (81%), behavioral symptoms (69%), intellectual disability (64%), epilepsy (62%), and motor delay (56%). Epilepsy types were variable, with West syndrome observed in three patients, generalized tonic–clonic seizures in two, and other subtypes observed in one individual each. Our findings suggest that, in line with other CHD-related disorders, heterozygous CHD5 variants are associated with a variable neurodevelopmental syndrome that includes intellectual disability with speech delay, epilepsy, and behavioral problems as main features.

Tryptophan degradation is associated with risk-taking propensity in methamphetamine users with treated HIV infection - Jared Lee; Ji-Young Lee; Christina S. Meade; Michael Cohn; Antonio Chahine; Samantha E. Dilworth; Jessica F. Magidson; Hetta Gouse; Dietmar Fuchs; Adam W. Carrico (Journal of NeuroVirology, 2020)

Combined effects of goethite nanoparticles with metallic contaminants and an organophosphorus pesticide on Eisenia andrei - Marcela I. Cáceres-Wenzel; Julio S. Fuchs; Florencia N. Bernassani; Adriana C. Cochón (Environmental Science and Pollution Research, 2020)

MDH1 deficiency is a metabolic disorder of the malate–aspartate shuttle associated with early onset severe encephalopathy - Melissa H. Broeks; Hanan E. Shamseldin; Amal Alhashem; Mais Hashem; Firdous Abdulwahab; Tarfa Alshedi; Iman Alobaid; Fried Zwartkruis; Denise Westland; Sabine Fuchs; Nanda M. Verhoeven-Duif; Judith J. M. Jans; et al. (Human Genetics, 2019)

Influence of genetic variation in the vitamin D pathway on plasma 25-hydroxyvitamin D3 levels and survival among patients with metastatic colorectal cancer - Chen Yuan; Lindsay Renfro; Pratibha B. Ambadwar; Fang-Shu Ou; Howard L. McLeod; Federico Innocenti; Jeffrey A. Meyerhardt; Brian M. Wolpin; Richard M. Goldberg; Axel Grothey; Charles S. Fuchs; Kimmie Ng (Cancer Causes & Control, 2019)

Calcium intake and colon cancer risk subtypes by tumor molecular characteristics - NaNa Keum; Li Liu; Tsuyoshi Hamada; Zhi Rong Qian; Jonathan A. Nowak; Yin Cao; Annacarolina da Silva; Keisuke Kosumi; Mingyang Song; Daniel Nevo; Molin Wang; Andrew T. Chan; et al. (Cancer Causes & Control, 2019)

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA) - S M Bergmann; Q Wang; W Zeng; Y Li; Y Wang; M Matras; M Reichert; D Fichtner; M Lenk; T Morin; N J Olesen; H F Skall; et al. (Journal of Fish Diseases, 2017)
Koi herpesvirus ( KHV ) causes KHV disease ( KHVD ). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti‐ KHV antibodies have not yet been fully validated for KHV . Therefore, it was developed and validated an enzyme‐linked immunosorbent assay ( ELISA ) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay conditions. It demonstrated high diagnostic and analytical sensitivity and specificity and was particularly useful at the pond or farm levels. Considering the scale of the carp and koi industry worldwide, this assay represents an important practical tool for the indirect detection of KHV , also in the absence of clinical signs.

Cytogenetic comparison of heteromorphic and homomorphic sex chromosomes in Coccinia (Cucurbitaceae) points to sex chromosome turnover - Aretuza Sousa; Jörg Fuchs; Susanne S. Renner (Chromosome Research, 2017)

Lithological mapping with multispectral data – setup and application of a spectral database for rocks in the Balakot area, Northern Pakistan - Michael Fuchs; Adnan A. Awan; Sardar S. Akhtar; Ijaz Ahmad; Simon Sadiq; Asif Razzak; Naghmah Haider (Journal of Mountain Science, 2017)

A bibliometric-based evaluation on environmental research in the Arab world - SH. H. Zyoud; D. Fuchs-Hanusch; S. H. Zyoud; A. E. Al-Rawajfeh; H. Q. Shaheen (International Journal of Environmental Science and Technology, 2017)

Cirrhotic patients have good insight into their daily functional impairment despite prior hepatic encephalopathy: comparison with PROMIS norms - Jasmohan S. Bajaj; Melanie B. White; Ariel B. Unser; Dinesh Ganapathy; Andrew Fagan; Edith A. Gavis; Richard K. Sterling; Douglas M. Heuman; Scott Matherly; Puneet Puri; Arun J. Sanyal; Velimir Luketic; et al. (Metabolic Brain Disease, 2016)

The amino-terminal domain of ORF149 of koi herpesvirus is preferentially targeted by IgM from carp populations surviving infection - F. Torrent; A. Villena; P. A. Lee; W. Fuchs; S. M. Bergmann; J. M. Coll (Archives of Virology, 2016)

A prospective study of oral contraceptive use and colorectal adenomas - Brittany M. Charlton; Edward Giovannucci; Charles S. Fuchs; Andrew T. Chan; Jung Eun Lee; Yin Cao; Stacey A. Missmer; Bernard A. Rosner; Susan E. Hankinson; Walter Willett; Kana Wu; Karin B. Michels (Cancer Causes & Control, 2016)

Television watching and colorectal cancer survival in men - Yin Cao; Jeffrey A. Meyerhardt; Andrew T. Chan; Kana Wu; Charles S. Fuchs; Edward L. Giovannucci (Cancer Causes & Control, 2015)

Enhancement of functional connectivity, working memory and inhibitory control on multi-modal brain MR imaging with Rifaximin in Cirrhosis: Implications for the gut-liver-brain axis - Vishwadeep Ahluwalia; James B. Wade; Douglas M. Heuman; Thomas A. Hammeke; Arun J. Sanyal; Richard K. Sterling; R. Todd Stravitz; Velimir Luketic; Mohammad S. Siddiqui; Puneet Puri; Michael Fuchs; Micheal J. Lennon; et al. (Metabolic Brain Disease, 2014)

CASPASE-12 and rheumatoid arthritis in African-Americans - Laura Marshall; Mohammad Obaidullah; Trista Fuchs; Naomi S. Fineberg; Garland Brinkley; Ted R. Mikuls; S. Louis Bridges; Evan Hermel (Immunogenetics, 2014)

Holocene river and slope activity in the Visoko Basin, Bosnia‐ H erzegovina – climate and land‐use effects - S. DREIBRODT; C. LUBOS; R. HOFMANN; N. MÜLLER‐SCHEEßEL; I. RICHLING; O. NELLE; M. FUCHS; K. RASSMANN; Z. KUJUNDŽIĆ‐VEJZAGIĆ; H.‐R. BORK; J. MÜLLER (Journal of Quaternary Science, 2013)
Alluvial and colluvial deposits were investigated at prehistoric tells close to the Bosna River. The chronology is based on ten radiocarbon ages, five optically stimulated luminescence ages, and on the archaeological record. Fluvial activity of the Bosna River is indicated by overbank fines [ca. 5000 (±1000) BC , 500 BC until today] and a phase of lateral displacement of the river bed with subsequent channel fills ca. 2000–500 BC . Early Holocene fluvial activity was probably triggered by climatic variability but might have promoted the expansion of Neolithic societies into the Visoko Basin. Mid‐ to late Holocene river activity occurred under increased climatic aridity but coincided with the expansion of prehistoric settlements to a wider area of the river basin on hard rocks in the adjacent mountainous areas. The destruction of the thin soil cover in the mountains is discussed as a probable trigger for enduring subsequent river activity. This is also indicated by a change in the geochemical signature of the alluvial sediments. The proposed mechanism might explain the mid to late Holocene river history in other regions. The potential of geochemical analyses and diachronous high‐resolution archaeological records to make inferences regarding sediment sources and geomorphological processes is demonstrated. Copyright © 2013 John Wiley & Sons, Ltd.

A structured approach to enhance flood hazard assessment in mountain streams - B. Mazzorana; F. Comiti; S. Fuchs (Natural Hazards, 2013)

Prospective cohort studies of bowel movement frequency and laxative use and colorectal cancer incidence in US women and men - Xuehong Zhang; Kana Wu; Eunyoung Cho; Jing Ma; Andrew T. Chan; Xiang Gao; Walter C. Willett; Charles S. Fuchs; Edward L. Giovannucci (Cancer Causes & Control, 2013)

Prediagnostic plasma vitamin B6 (pyridoxal 5′-phosphate) and survival in patients with colorectal cancer - Youjin Je; Jung Eun Lee; Jing Ma; Xuehong Zhang; Eunyoung Cho; Bernard Rosner; Jacob Selhub; Charles S. Fuchs; Jeffrey Meyerhardt; Edward Giovannucci (Cancer Causes & Control, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Evaluation of Tetrahydrobiopterin Pathway in Operating Room Workers: Changes in Biopterin Status and Tryptophan Metabolism - Mustafa Baydar; Zeynep Capan; Gozde Girgin; S. Sezin Palabiyik; Gonul Sahin; Dietmar Fuchs; Terken Baydar (Bulletin of Environmental Contamination and Toxicology, 2012)

An in vivo neovascularization assay for screening regulators of angiogenesis and assessing their effects on pre-existing vessels - Witold W. Kilarski; Ludvig Petersson; Peder Fredlund Fuchs; Marcin S. Zielinski; Pär Gerwins (Angiogenesis, 2012)

A dietary pattern that is associated with C-peptide and risk of colorectal cancer in women - Teresa T. Fung; Frank B. Hu; Matthias Schulze; Michael Pollak; Tianying Wu; Charles S. Fuchs; Edward Giovannucci (Cancer Causes & Control, 2012)

Plasma folate, methylenetetrahydrofolate reductase (MTHFR), and colorectal cancer risk in three large nested case–control studies - Jung Eun Lee; Esther K. Wei; Charles S. Fuchs; David J. Hunter; I-Min Lee; Jacob Selhub; Meir J. Stampfer; Walter C. Willett; Jing Ma; Edward Giovannucci (Cancer Causes & Control, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

A prospective study of intakes of zinc and heme iron and colorectal cancer risk in men and women - Xuehong Zhang; Edward L. Giovannucci; Stephanie A. Smith-Warner; Kana Wu; Charles S. Fuchs; Michael Pollak; Walter C. Willett; Jing Ma (Cancer Causes & Control, 2011)

Tropomyosin is in a reduced state in rat cardiac muscle - Sherwin S. Lehrer; Socheata Ly; Franklin Fuchs (Journal of Muscle Research and Cell Motility, 2011)

Tropomyosin is in a reduced state in rabbit psoas muscle - Sherwin S. Lehrer; Socheata Ly; Franklin Fuchs (Journal of Muscle Research and Cell Motility, 2011)

Ammonium and attachment of Rhodopirellula baltica - Carsten S. Frank; Philipp Langhammer; Bernhard Maximilian Fuchs; Jens Harder (Archives of Microbiology, 2011)

In vitro testing for anti-inflammatory properties of compounds employing peripheral blood mononuclear cells freshly isolated from healthy donors - M. Jenny; M. Klieber; D. Zaknun; S. Schroecksnadel; K. Kurz; M. Ledochowski; H. Schennach; Dietmar Fuchs (Inflammation Research, 2011)

MGMT promoter methylation, loss of expression and prognosis in 855 colorectal cancers - Kaori Shima; Teppei Morikawa; Yoshifumi Baba; Katsuhiko Nosho; Maiko Suzuki; Mai Yamauchi; Marika Hayashi; Edward Giovannucci; Charles S. Fuchs; Shuji Ogino (Cancer Causes & Control, 2011)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Germline polymorphisms in the one-carbon metabolism pathway and DNA methylation in colorectal cancer - Aditi Hazra; Charles S. Fuchs; Takako Kawasaki; Gregory J. Kirkner; David J. Hunter; Shuji Ogino (Cancer Causes & Control, 2010)

Association of the TCF7L2 polymorphism with colorectal cancer and adenoma risk - Aditi Hazra; Charles S. Fuchs; Andrew T. Chan; Edward L. Giovannucci; David J. Hunter (Cancer Causes & Control, 2008)

A microdiversity study of anammox bacteria reveals a novel Candidatus Scalindua phylotype in marine oxygen minimum zones - Dagmar Woebken; Phyllis Lam; Marcel M. M. Kuypers; S. Wajih A. Naqvi; Boran Kartal; Marc Strous; Mike S. M. Jetten; Bernhard M. Fuchs; Rudolf Amann (Environmental Microbiology, 2008)
Summary The anaerobic oxidation of ammonium (anammox) contributes significantly to the global loss of fixed nitrogen and is carried out by a deep branching monophyletic group of bacteria within the phylum Planctomycetes . Various studies have implicated anammox to be the most important process responsible for the nitrogen loss in the marine oxygen minimum zones (OMZs) with a low diversity of marine anammox bacteria. This comprehensive study investigated the anammox bacteria in the suboxic zone of the Black Sea and in three major OMZs (off Namibia, Peru and in the Arabian Sea). The diversity and population composition of anammox bacteria were investigated by both, the 16S rRNA gene sequences and the 16S‐23S rRNA internal transcribed spacer (ITS). Our results showed that the anammox bacterial sequences of the investigated samples were all closely related to the Candidatus Scalindua genus. However, a greater microdiversity of marine anammox bacteria than previously assumed was observed. Both phylogenetic markers supported the classification of all sequences in two distinct anammox bacterial phylotypes: Candidatus Scalindua clades 1 and 2. Scalindua 1 could be further divided into four distinct clusters, all comprised of sequences from either the Namibian or the Peruvian OMZ. Scalindua 2 consisted of sequences from the Arabian Sea and the Peruvian OMZ and included one previously published 16S rRNA gene sequence from Lake Tanganyika and one from South China Sea sediment (97.9–99.4% sequence identity). This cluster showed only ≤ 97% sequence identity to other known Candidatus Scalindua species. Based on 16S rRNA gene and ITS sequences we propose that the anammox bacteria of Scalindua clade 2 represent a novel anammox bacterial species, for which the name Candidatus Scalindua arabica is proposed. As sequences of this new cluster were found in the Arabian Sea, the Peruvian OMZ, in Lake Tanganyika and in South China sediment, we assume a global distribution of Candidatus Scalindua arabica as it is observed for Candidatus Scalindua sorokinii/brodae (or Scalindua clade 1).

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Microbial control of phosphate in the nutrient‐depleted North Atlantic subtropical gyre - Mikhail V. Zubkov; Isabelle Mary; E. Malcolm S. Woodward; Phillip E. Warwick; Bernhard M. Fuchs; David J. Scanlan; Peter H. Burkill (Environmental Microbiology, 2007)
Summary Little is known about the dynamics of dissolved phosphate in oligotrophic areas of the world's oceans, where concentrations are typically in the nanomolar range. Here, we have budgeted phosphate uptake by the dominant microbial groups in order to assess the effect of the microbial control of this depleted nutrient in the North Atlantic gyre. Low concentrations (2.2 ± 1.2 nM) and rapid microbial uptake (2.1 ± 2.4 nM day −1 ) of bioavailable phosphate were repeatedly determined in surface waters of the North Atlantic oligotrophic gyre during spring and autumn research cruises, using a radiotracer dilution bioassay technique. Upper estimates of the concentration of bioavailable phosphate were 7–55% of the dissolved mineral phosphate suggesting that a considerable part of the chemically measured nanomolar phosphate was in a form unavailable for direct microbial uptake. A 1:1 relationship ( r 2 = 0.96, P Prochlorococcus phototrophic cyanobacteria, were the two major competing groups for bioavailable phosphate. These heterotrophic bacteria had low nucleic acid content and 60% of them comprised of SAR11 clade cells based on the results of fluorescence in situ hybridization. Each of the two competing bacterial groups was responsible for an average of 45% of the phosphate uptake, while Synechococcus cyanobacteria (7%) and picoplanktonic algae (0.3%) played minor roles in direct phosphate uptake. We have demonstrated that phosphate uptake in the oligotrophic gyre is rapid and dominated by two bacterial groups rather than by algae.

Effects of turbulence‐mediated larval behavior on larval supply and settlement in tidal currents - Heidi L. Fuchs; Michael G. Neubert; Lauren S. Mullineaux (Limnology and Oceanography, 2007)
Intertidal gastropod larvae retract their vela and sink in strong turbulence, and this behavior potentially increases settlement in turbulent coastal habitats. We incorporated turbulence‐induced sinking behavior of mud snail larvae ( Ilyanassa obsoleta ) in a vertical advection‐diffusion model to characterize behavioral effects on larval supply and settlement in a tidal channel. Throughout flood and ebb tides, larvae that sink in turbulence have higher near‐bed concentrations than passive larvae. This high supply of larvae enables behaving larvae to settle more successfully than passive larvae in strong currents characteristic of tidal inlets. Unlike passive larvae, those that sink in turbulence settle more successfully in stronger currents than in weaker ones and would concentrate their settlement in energetic tidal zones. Turbulence‐mediated behavior may give intertidal larvae a greater ability to select habitats and may reduce larval mortality rates due to settlement failure.

A Prospective Study of Body Mass Index, Hypertension, and Smoking and the Risk of Renal Cell Carcinoma (United States) - Keith T. Flaherty; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Frank E. Speizer; Walter C. Willett; Gary C. Curhan (Cancer Causes & Control, 2005)

Sinking behavior of gastropod larvae ( Ilyanassa obsoleta ) in turbulence - Heidi L. Fuchs; Lauren S. Mullineaux; Andrew R. Solow (Limnology and Oceanography, 2004)
Larvae of coastal gastropods sink in turbulence and may use nearshore turbulence as an initial settlement cue. Our objective was to quantify the relationship between turbulence and the proportion of sinking larvae for competent mud snail veligers ( Ilyanassa obsoleta ). We exposed larvae to a range of field‐relevant turbulence conditions (ɛ = 8.1 × 10 −3 to 2.7 × 10 0 cm 2 s −3 ) in a grid‐stirred tank, holding other factors constant. We used a video plankton recorder to record larval movements in still water and in turbulence. Larval trajectories and velocity measurements were extracted using video‐image analysis. We also measured turbulent flow velocities independently, using laser Doppler velocimetry. To interpret empirical measurements in terms of larval behavior, we developed a threecomponent, normal mixture model for vertical velocity distributions of larvae in turbulence. The model was fitted to observed larval velocities by maximum likelihood, to estimate the proportions of sinking, hovering, and swimming larvae. Over the range of turbulence intensities found in typical coastal habitats, the proportion of sinking larvae increased exponentially ( r 2 = 0.89) with the log of the turbulence dissipation rate. The net mean behavioral velocity of the larvae shifted from positive to negative when the dissipation rate reached ~10 −1 cm 2 s −3 . By sinking when they enter turbulent, shallow water, competent larvae could improve their chances of settling in favorable coastal habitats.

Exploring the method of optical dating and comparison of optical and 14 C ages of Late Weichselian coversands in the southern Netherlands - D. Vandenberghe; C. Kasse; S. M. Hossain; F. De Corte; P. Van Den Haute; M. Fuchs; A. S. Murray (Journal of Quaternary Science, 2004)
A study was made of the applicability of three different techniques for equivalent dose ( D e ) determination in the optical dating of quartz: the single‐aliquot regenerative‐dose technique (SAR), the single‐aliquot additive‐dose technique (SAAD) and the multiple‐aliquot additive‐dose technique (MAAD). For this purpose, quartz grains were extracted from a sequence of Upper Pleniglacial to Late‐glacial coversands exposed at the locality of Ossendrecht in the southwestern Netherlands, a site for which both radiocarbon and earlier luminescence dates are available, providing independent age control. Upon testing the different assumptions underlying each of the three OSL techniques investigated, the SAR protocol was found to be the technique of choice. The optical ages obtained with this protocol were in good agreement with the chronostratigraphical position of the sediments investigated and with the available chronostratigraphical information on the same and equivalent deposits. This confirms the suitability of the SAR technique for dating coversands. Furthermore, a small laboratory intercomparison of SAR‐based D e determinations yielded results that were in fair overall agreement. Copyright © 2004 John Wiley & Sons, Ltd.

Aspirin, other NSAIDs, and ovarian cancer risk (United States) - Kathleen M. Fairfield; David J. Hunter; Charles S. Fuchs; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2002)

Ecotoxicological Characterization of a Disposal Lagoon from a Munition Plant - J. S. Fuchs; M. L. Oneto; N. B. Casabé; O. Gómez Segura; R. Tarulla; M. Vaccarezza; C. Sánchez-Rivas; E. M. Kesten; E. J. Wood (Bulletin of Environmental Contamination and Toxicology, 2001)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Debris removal by head-pushing in A. florea Fabr. honeybees - M. Sen Sarma; S. Fuchs; J. Tautz (The Science of Nature, 2000)

Lack of Effect of Antibiotic Resistance on Susceptibility of Microorganisms to Chlorhexidine Gluconate or Povidone Iodine - A. L. Barry; P. C. Fuchs; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Antibacterial Activity of Moxifloxacin (Bay 12-8039) against Aerobic Clinical Isolates, and Provisional Criteria for Disk Susceptibility Tests - S. D. Brown; A. L. Barry; P. C. Fuchs (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Flight machinery dimensions of honeybees, Apis mellifera - H. R. Hepburn; S. E. Radloff; S. Fuchs (Journal of Comparative Physiology B, 1999)

Evolution of extreme polyandry in the honeybee Apis mellifera L. - S. Fuchs; R. F. A. Moritz (Behavioral Ecology and Sociobiology, 1999)

Behavioral interactions produced by co-administration of 7-OH-DPAT with cocaine or apomorphine in the rat - Taline V. Khroyan; Rita A. Fuchs; Alex M. Beck; Robert S. Groff; J. L. Neisewander (Psychopharmacology, 1999)

Esterases of Corbicula fluminea as Biomarkers of Exposure to Organophosphorus Pesticides - S. B. Basack; M. L. Oneto; J. S. Fuchs; E. J. Wood; E. M. Kesten (Bulletin of Environmental Contamination and Toxicology, 1998)

Screening endoscopy and risk of colorectal cancer in United States men - Charles S. Fuchs; Edward L. Giovannucci; Graham A. Colditz; Anne M. Kavanagh (Cancer Causes & Control, 1998)

Provisional Quality Control Parameters and Interpretive Criteria for Testing Susceptibility of Streptococcus pneumoniae and Haemophilus influenzae to Quinupristin/Dalfopristin (RP59500) - P. Fuchs; A. Barry; S. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Provisional quality control parameters and interpretive criteria for testing susceptibility ofStreptococcus pneumoniae andHaemophilus influenzae to quinupristin/dalfopristin (RP59500) - P. Fuchs; A. Barry; S. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Predictive validity of the extinction/reinstatement model of drug craving - Rita A. Fuchs; L. T. L. Tran-Nguyen; Sheila E. Specio; Robert S. Groff; J. L. Neisewander (Psychopharmacology, 1998)

Parity and other reproductive factors and risk of adenomatous polyps of the distal colorectum (United States) - Elizabeth A. Platz; Maria Elena Martinez; Francine Grodstein; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Edward Giovannucci (Cancer Causes & Control, 1997)

In vitro activity of the new ketolide HMR 3004 compared to an azalide and macrolides againstStreptococcus pneumoniae andHaemophilus influenzae - A. L. Barry; P. C. Fuchs; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Anaerobic metabolism of l -phenylalanine via benzoyl-CoA in the denitrifying bacterium Thauera aromatica - Sabine Schneider; M. E.-S. Mohamed; G. Fuchs (Archives of Microbiology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Susceptibility testing quality control studies with fosfomycin tromethamine - P. C. Fuchs; A. L. Barry; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

In vitro activity of an orally administered streptogramin (RPR 106,972) compared to quinupristin/dalfopristin and erythromycin - A. L. Barry; P. C. Fuchs; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Coordination dynamics of trajectory formation - J. J. Buchanan; J. A. S. Kelso; A. Fuchs (Biological Cybernetics, 1996)

Coordination dynamics of trajectory formation - J. J. Buchanan; J. A. S. Kelso; A. Fuchs (Biological Cybernetics, 1995)

Choice in Varroa jacobsoni Oud. between honey bee drone or workerbrood cells for reproduction - S. Fuchs (Behavioral Ecology and Sociobiology, 1992)

Carbon assimilation by the autotrophic thermophilic archaebacterium Thermoproteus neutrophilus - S. Schfer; C. Barkowski; G. Fuchs (Archives of Microbiology, 1986)

An informational analysis of the alarm communication by drumming behavior in nests of carpenter ants (Camponotus, Formicidae, Hymenoptera) - S. Fuchs (Behavioral Ecology and Sociobiology, 1976)

The response to vibrations of the substrate and reactions to the specific drumming in colonies of carpenter ants (Camponotus, Formicidae, Hymenoptera) - S. Fuchs (Behavioral Ecology and Sociobiology, 1976)